The Case for the Fundamental MBH-σ Relation - Marsden, Christopher; Shankar, Francesco; Ginolfi, Mitchele; Zubovas, Kastytis (Frontiers in Physics, 2020)
Strong scaling relations between host galaxy properties (such as stellar mass, bulge mass, luminosity, effective radius etc) and their nuclear supermassive black hole's mass point towards a close coevolution. In this work, we present a review of previous efforts supporting the fundamental importance of the relation between supermassive black hole mass and stellar velocity dispersion (M-sigma), and present further original work supporting this claim via analysis of residuals and principal component analysis. We also review the main theoretical scenarios in favour of the existence of a M-sigma relation, showing this relation has a strong theoretical precedent.